Evaluasi Reklamasi di Area Pertambangan Batubara PT. PQ, Kecamatan Tanjung Kidul, Kabupaten Muara Enim, Provinsi Sumatera Selatan - Esthi Kusdarini; Eka Rizky Ramadhani; Fairus Atika Redanto Putri (Dinamika Lingkungan Indonesia, 2023)
Coal mining activities carried out by PT. PQ causes a change in the environmental setting so that its function needs to be restored according to its designation. The return of land function is carried out through reclamation activities. Reclamation activities need to be evaluated in order to continue to make improvements and optimal results. This study assesses the success rate of reclamation carried out by PT. PQ. This study aims to examine and evaluate the reclamation activities carried out by PT. PQ is based on Decree of the Minister of Energy and Mineral Resources Number 1827/30 K/MEM of 2018. The research method used is field observation; analysis of primary and secondary data on land use, revegetation, and maintenance stages; and mathematical calculation of reclamation success rate. Soil quality was tested by testing the pH of H2O, organic C, and total N. The results showed that the soil in the reclamation area is considered to be acidic, namely the pH of H2O is 4.5 -5.5; organic C by 1-2%; N total of 0.1 – 0.2%; C/N of 5 – 1 test for pH H2O, organic C, and N total reclamation success rate of 94.1 or in the good category. The soil in the reclamation area has a pH of 4.3 and a soil organic C content of less than 1%. The main eucalyptus oil plants require soil with a pH of 4.5 -5.5. organic C by 1-2%; N total of 0.1 – 0.2%; C/N of 5 – 1. To complete the reclamation activities, it is necessary to increase the pH of the soil, which is still acidic, namely 4.3 and to increase the organic C content of the soil, which is still low, namely <1%. Findings of acidic soil pH and soil organic C content below the standard needed for the main plant eucalyptus oil are initial information for improving soil conditions in the reclamation area of PT. PQ so that reclamation activities run better.